Feasibility of natural brooding of quail eggs by broody hen - Lata, Kanak; Srivastava, R C (Indian Farming, 2015)
Backyard quail rearing can be done at farmers’ level through natural brooding by hen. Number of eggs per brooding hen were 20-25 eggs. It will solve the problems, i.e. reducing drudgery, excess stress, minimizing transportation and brooding cost and time saving etc. Quail farming can be popularized in scattered and proper transportation lacking islands through this technology, which can be a source of better livelihood in these Islands.